Serum proteomics study reveals candidate biomarkers for systemic lupus erythematosus - Zhong, Lijun (Int J Clin Exp Pathol, 2017)
Systemic lupus erythematosus (SLE) is an autoimmune disease which is characterized by the presence of autoantibodies. It will be helpful if specific serum biomarkers can be used for monitoring the disease activity as well as differentiating SLE from other diseases. For this purpose, we used a label free-based two dimensional liquid chromatography mass spectrometry platform to analyze serum samples from SLE patients in active or inactivestage. Significant differences were found for 42 serum proteins implicated in pathways including complement and coagulation cascades. Further gene set enrichment analysis revealed that gene sets including formation of fibrin clot, ECM glycoproteins and innate immune system were highly correlated with the SLE disease activity. To further assess the validity of these findings, thrombospondin-4 was selected for subsequent ELISA assays. We also explored the autoantibody of three candidate biomarkers in larger cohorts including SLE, Rheumatoid arthritis, Sjogrensyndrome patients and normal controls. Our findings provided valuable information on the proteomic changes in the serum of different SLE disease activity. Serum properdin, collectin-11 and thrombospondin-4 were valuable in monitoring the disease activity of SLE, and the autoantibodies to them may be valuable in differentiating SLE from other diseases for clinical diagnosis in the future.